Supervision in child protection: a space and place for reflection or an excruciating marathon of compliance?. Issue 3 (4th May 2022) - Beddoe, Liz; Ferguson, Harry; Warwick, Lisa; Disney, Tom; Leigh, Jadwiga; Cooner, Tarsem Singh
ABSTRACT: Supervision is promoted as an essential element of effective professional practice in social work. Its benefits include promoting reflective social work and assisting with the management of the emotions generated in challenging practice. This article reports on the observations of supervision in a 15-month ethnographic study of social work teams on two very different sites in England, one using hot-desking the other a small team design. Our findings show how supervision is constituted by temporal, spatial and relational elements and that some current organisational designs do not create the ideal environment for reflective supervision to flourish. Far from providing an opportunity for containment of challenging emotions, supervision was sometimes a source of stress. It was experienced as reflective and containing where managers were accessible and space was made for thinking in a context of openness that encouraged regular deep conversations about current work. By experiencing the atmospheres of supervisory encounters and organisational cultures, this study has enabled us to produce new insights into the embodied nature of supervision as it is lived.